2022
DOI: 10.1177/02762366211070999
|View full text |Cite
|
Sign up to set email alerts
|

Varieties of Inner Speech and Creative Potential

Abstract: Inner speaking, the covert talking that goes on inside a person's mind, can shape creative thought. How the phenomenological properties and quality of inner speaking correlate with a person's creative potential, however, is an open scientific problem. To explore this, participants ( n = 267) filled in the revised Varieties of Inner Speech Questionnaire and the revised Launay Slade Hallucination Scale (auditory subscale), and performed three tests of creative potential: one divergent (Alternative Uses Test) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 118 publications
1
15
0
Order By: Relevance
“…If we want to make public transport more attractive, for example, information about roller coaster rides is more likely affords generating creative ideas than merely relying on information about known public transport services; and when the roller coaster theme is exhausted, or information with more potential for creativity comes into view, the cycle repeats. Inner speaking, here, can be seen as a form of action that both characterizes and influences this process of idea generation (de Rooij, 2022b; Hellerstein, 2009).…”
Section: Inner Speakingmentioning
confidence: 99%
See 3 more Smart Citations
“…If we want to make public transport more attractive, for example, information about roller coaster rides is more likely affords generating creative ideas than merely relying on information about known public transport services; and when the roller coaster theme is exhausted, or information with more potential for creativity comes into view, the cycle repeats. Inner speaking, here, can be seen as a form of action that both characterizes and influences this process of idea generation (de Rooij, 2022b; Hellerstein, 2009).…”
Section: Inner Speakingmentioning
confidence: 99%
“…While many aspects of inner speaking can characterize and affect idea generation, such as the role of dialogue or how condensed inner speaking is (de Rooij, 2022b), the role of inner speaking in self‐regulation might be particularly impactful. Self‐regulation broadly entails the strategies that people use to adaptively influence their thinking, emotional, and motivational states (Ivcevic & Nusbaum, 2017), and explains a large portion of the variance in creative activity and achievement (Zielińska, Forthmann, Lebuda, & Karwowski, 2023).…”
Section: Inner Speakingmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Racy et al (2022) found positive correlations between the VISQ-R and self-talk frequency, inner experiences such as inner speaking and seeing, use of private speech for self-regulatory and self-reflection purposes, and with subjective perceived frequency of inner speech content and function. In a study that examined the relationship between inner speech and creativity ( de Rooij, 2022 ), the Condensed and Evaluative/Critical subscales of the VISQ-R were found to be negatively correlated with some aspects of creativity, while other subscales did not show any correlations with creative potential. Taken together, these findings show the convergent and divergent validity of the VISQ-R.…”
Section: Introductionmentioning
confidence: 99%